Hamish Macbeth. Series one [videorecording (DVD)] - Keir, Deirdre; Renton, Nicholas; Boyle, Daniel; Carlyle, Robert, 1961-; Beaton, M. C.; Lunn, John (BBC VIdeo ; Distributed by Warner Home Video, 2005)
Police constable Hamish Macbeth keeps the peace in the small Scottish town of Lochdubh in his own unique way.